Juvenile Delinquents And Dar Al-Islah Guidance Programs In Oman: Analytical Descriptive Study - Abdul Hakim Abdullah Salem Al-Ghailani; Mahmoud Mohamed Ali Mahmoud Edris (Usuli Faqih Research Centre PLT, 2024)
Vol. 14 No. 1